The mathematics of various entertaining subjects. - Beineke, Jennifer Elaine, 1969-; Rosenhouse, Jason (Princeton University Press ; Published in association with the National Museum of Mathematics, 2017)
The history of mathematics is filled with major breakthroughs resulting from solutions to recreational problems. Problems of interest to gamblers led to the modern theory of probability, for example, and surreal numbers were inspired by the game of Go. Yet even with such groundbreaking findings and a wealth of popular-level books, research in recreational mathematics has often been neglected. This book returns with a brand-new compilation of fascinating problems and solutions in recreational mathematics. It gathers together the top experts in recreational math and presents a compelling look at board games, card games, dice, toys, computer games, and much more. The book is divided into five parts: puzzles and brainteasers, geometry and topology, graph theory, games of chance, and computational complexity. Readers will discover what origami, roulette wheels, and even the game of Trouble can teach about math. Chapters contain new results, and include short expositions on the topic's background, providing a framework for understanding the relationship between serious mathematics and recreational games. Mathematical areas explored include combinatorics, logic, graph theory, linear algebra, geometry, topology, computer science, operations research, probability, game theory, and music theory.
Keywords: Mathematical recreations -- Research.; Jeux mathématiques -- Recherche.; GAMES -- Reference.; GAMES -- Travel Games.; MATHEMATICS -- Recreations & Games.; Bernard Frenicle de Bessy.; Central Circle.; Clickomania.; Euclidean geometry.; Hasbro.; Le Professeur N. Claus.; Leonhard Euler.; Lewis Carroll.; Matrix Tree Theorem.; Multinational War.; Penney's Game.; Percy MacMahon.; Pop-O-Matic Trouble.; Raymond Smullyan.; Tangle.; Tower of Hanoi.; algebraic graph theory.; board games.; children's card games.; classical logic.; coin-flipping.; coloring.; combinatorics.; computer games.; computer science.; counting problems.; counting trees.; crossing numbers.; cubes.; distributed processing.; dragons.; duels.; game theory.; geometry.; graph theory.; graphs.; gruels.; integer programming.; iterative duels.; kasha.; linear algebra.; logic puzzles.; logic.; magic constant.; magic squares.; math.; mathematical puzzles.; music.; musical arrangement.; nine-point circle.; nonclassical logics.; orthocenter.; paper folding.; prisoners.; probability.; recreational mathematics.; representation theory.; roulette wheel.; spanning tree.; topology.; triangles.; truels.; twenty-sided dice.; Éduard Lucas.